FORECASTING OF RAMBUTAN PRICES VIA THE USE OF STATISTICAL METHODS - Riansut , Warangkhana (Srinakharinwirot University Journal of Sciences and Technology, 2023)
The objective of this study was to forecast the rambutan prices via the use of statistical methods. The monthly average data, which were gathered from the website of the Office of Agricultural Economics during January 2005 to May 2020 (185 months) were divided into 2 datasets. The first dataset, which consisted of 180 months from January 2005 to December 2019 was used for constructing the forecasting models via the use of 10 statistical methods. The second dataset, which consisted of 5 months from January to May 2020 was used for comparing the accuracy of the forecasting model via the lowest root mean square error. The results indicated that the most accurate method was the combining forecasts method with a model: t = 2.83552 + 1.11825SimpleS - 0.26902WinterAdd. This forecast model had a forecast error of only 3.34 Baht/kg. Therefore it can be used as a guideline for farmers and rambutan production agencies to plan the planting accordingly.